Analisis Sistem yang Memengaruhi Tingkat Pengeluaran Kas PT Bintang Energi Sejahtera - Rizky, Wahyu Adinda; Andhaniwati, Erry (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to evaluate the factors that influence the level of cash expenditure at PT Bintang Energi Sejahtera. This research identifies and analyzes major spending categories, significant monthly fluctuations, and compares annual spending. By analyzing cash disbursement report data for the last two years, this research found that operational expenditure is the largest category. These findings highlight the importance of effective operational cost management to maintain company financial stability. The increase in spending from year to year indicates the need for budget adjustments and wiser financial strategies. This research also identifies potential financial risks that may arise, helping companies design more appropriate risk mitigation strategies. The results of this research provide a strong basis for PT Bintang Energi Sejahtera to increase the efficiency of cash expenditure, which can ultimately improve the company's financial performance. By understanding spending patterns, companies can make more accurate projections, identify areas that can be optimized, and plan cash allocation better. It is also hoped that this research will be a valuable reference for other companies facing similar challenges in managing their cash expenditures, as well as contribute to improving financial knowledge and practices in the energy industry. This research provides an important contribution to the understanding of PT's financial performance. Bintang Energi Sejahtera and assist stakeholders in making more informed decisions. In this way, companies can become more resilient in facing financial crises and strengthen overall financial performance.